KONVERGENSI IFRS DI INDONESIA Seberapa Perlunya Dilakukan di Indonesia dan Bagaimanakah Pelaksanaannya? - Andrea G. Diliharto G. Diliharto (Universitas Bunda Mulia, 2017)
The financial statements are often referred to as the language of business. The financial statements provide information about the company's financial condition that can be used as a basis for decision-making for all stakeholders of the company. Investors or shareholders, as a major stakeholder, is very concerned about the numbers and all of the information presented in the financial statements, considering all these things are intimately associated with the fate of their investment. The good financial statements will be able to convey the message of the report concerning the financial condition of the business entity so that it can be understood by the various interested parties (stakeholders). In order to uniformity of financial statements, they held a generally accepted standard. The financial statements must be presented shall be in accordance with accounting principles and generally accepted financial reporting or Generally Accepted Accounting Principles (GAAP). An accepted accounting principles in a country area in general is not necessarily accepted in other countries. Nature of